A proposal of multicultural relation: Christian religious education and religious moderation - Rantung, Djoys A. (HTS teologiese studies, 2024)
The multicultural context of Indonesian society has prompted the idea of religious moderation as a defense mechanism for harmonious relations. However, peace, both in practice and academically, continues to evolve through various dialogues and studies to create a harmonious society. This study aims to present peace-based Christian religious education for religious moderation in Indonesia within the context of multicultural society. Using a descriptive qualitative analysis approach, various references such as books, articles and other sources are utilised as primary materials in constructing arguments. In conclusion, peace-based Christian religious education offers an alternative approach for religious moderation in Indonesia within its multicultural context.Contribution: This article supplies new insight to the religious moderation through Christian Religious Education pathway, which could share harmony and peace to the society with multicultural context in Indonesia. Also, the insight provides peace-based Christian religious education that could be linked to the study of religion and theology.